Poultry eggshell-derived antimicrobial materials: Current status and future perspectives. (15th July 2022) - Shang, Baoya; Wang, Shanshan; Lu, Lingxia; Ma, Huanhuan; Liu, Aiqi; Zupanic, Anze; Jiang, Ling; Elnawawy, Aml S.; Yu, Yadong
Abstract: Poultry eggs, the basic foodstuffs of human society, have been extensively consumed for domestic and industrial uses. A large amount of eggshell waste is generated and discarded every year, resulting in a waste of natural resources and a threat to the environment. In this context, the reutilization of eggshell waste has gained increasing attentions. Meanwhile, the overuse of antibiotics has led to the emergence of many drug-resistant bacteria, which greatly endangers public health. Therefore, manufacturing new materials with strong antimicrobial activities has become the focus of many researchers. Recent studies have revealed that eggshells can be applied as solid substances, the raw materials for calcium oxide, and the calcium source for synthesizing hydroxyapatite or other materials with antimicrobial activities. Herein, the preparation methods, antibacterial mechanisms and the applications of these eggshell waste-derived antibacterial materials are summarized in this review. Finally, the current challenges and future directions in this field are discussed. Highlights: Eggshells are excellent raw materials to prepare antibacterial agents. Preparing eggshell-derived antibacterial agents helps to recycle biological waste. Methods for preparing eggshell-derived antibacterial agents are summarized. Mechanisms and applications of eggshell-derived antibacterial agents are introduced.